2006
DOI: 10.1162/jocn.2006.18.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Surrounding Suppression and Facilitation in the Determination of Border Ownership

Abstract: Contextual modulation reported in early- to intermediate-level visual areas could be an essential component to signal border ownership (BO) that specifies the direction of figure along a contour. The surrounding regions that evoke significant suppression or facilitation are highly localized and asymmetric with respect to the center of the classical receptive field (CRF). We propose a hypothesis that such surrounding modulation is a basis for BO-selectivity. Although this idea has been discussed for several yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 30 publications
6
69
1
Order By: Relevance
“…4,5 A computational model that takes into account surrounding contrast, based on the surrounding modulation, has yielded high consistency and robustness for various stimuli in BO signaling. 6 Because models based on the surrounding modulation rely neither on completeness nor on smooth continuity, such models are consistent with the argument that gestalt factors might not be crucial for BO determination. As a step toward the understanding of neural mechanisms underlying the determination of BO, we psychophysically investigated the robustness of BO coding.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…4,5 A computational model that takes into account surrounding contrast, based on the surrounding modulation, has yielded high consistency and robustness for various stimuli in BO signaling. 6 Because models based on the surrounding modulation rely neither on completeness nor on smooth continuity, such models are consistent with the argument that gestalt factors might not be crucial for BO determination. As a step toward the understanding of neural mechanisms underlying the determination of BO, we psychophysically investigated the robustness of BO coding.…”
Section: Introductionsupporting
confidence: 63%
“…This strongly indicates that the BO-TAE originates from the fatigue of BO-selective cells. Simulation studies 6,13 have shown that most properties of BO-selective cells can be evoked from asymmetric distribution of facilitatory and suppressive surrounding regions reported in early vision. 14,15 For example, when a stimulus is placed onto a facilitatory region of a cell, it enhances the cell's responses, and therefore the cell behaves as if the contour is owned by the side where a facilitatory region is present.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the responses of border-ownership cells have been modeled as a result of pure feedforward operations (Heitger et al, 1994;Sakai and Nishimura, 2006;Supèr et al, 2010), of intraareal dynamics (Baek and Sajda, 2005;Zhaoping, 2005) and of feedforward and feedback interactions between areas (Craft et al, 2007;Jehee et al, 2007;Kogo et al, 2010), respectively. Our findings falsify pure feedforward models as they predict the same latencies of border-ownership signals regardless of the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…V1 and PP are linked mutually for the application of spatial attention to V1, and for the modification of spatial attention in PP. The V2 module determines DOF based on contrast gain that is extracted by the V1 module [2]. The PP represents spatial attention that will facilitate the contrast processes within the attended location in V1.…”
Section: Modelmentioning
confidence: 99%
“…Spatial attention alters local contrast gain in early vision, thus apparent local contrast will be modulated. If the local contrast is the basis for the determination of border-ownership (BO) that tells which side of a contour owns the border [1,2], BO will be modulated based on the local contrast that is altered by the attention. If the effect of attention is significant, the activity of BOselective cells will be facilitated/suppressed so that the DOF will be flipped.…”
Section: Introductionmentioning
confidence: 99%